2022
DOI: 10.1002/jum.16082
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Elastography for Detecting Calf Muscle Stiffness: An Effective Tool for Assessing Sarcopenia

Abstract: Objectives To explore the feasibility of shear wave elastography for evaluating sarcopenia. Methods The shear wave velocities (SWV) of the tibialis anterior, medial gastrocnemius, and soleus were measured in 130 subjects in the Second Affiliated Hospital of Fujian Medical University from January 2021 to June 2022. Consistency was evaluated in 20 cases using the intraclass correlation coefficient. According to the 2019 Asian Working Group for Sarcopenia(AWGS) diagnostic criteria, the patients were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
(66 reference statements)
1
3
0
Order By: Relevance
“…This finding suggests diminished intrinsic muscle stiffness in older adults, which is potentially indicative of muscle strength loss or sarcopenia. Agreeing with this finding, previous work found reduced structural stiffness in the triceps surae, tibialis anterior, quadriceps, and hamstrings in older adults (3739). Some of these studies further found that decreased muscle stiffness was related to lower muscle mass and increased rate of sarcopenia (38, 39).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…This finding suggests diminished intrinsic muscle stiffness in older adults, which is potentially indicative of muscle strength loss or sarcopenia. Agreeing with this finding, previous work found reduced structural stiffness in the triceps surae, tibialis anterior, quadriceps, and hamstrings in older adults (3739). Some of these studies further found that decreased muscle stiffness was related to lower muscle mass and increased rate of sarcopenia (38, 39).…”
Section: Discussionsupporting
confidence: 65%
“…Agreeing with this finding, previous work found reduced structural stiffness in the triceps surae, tibialis anterior, quadriceps, and hamstrings in older adults (37)(38)(39). Some of these studies further found that decreased muscle stiffness was related to lower muscle mass and increased rate of sarcopenia (38,39). Remarkably, the larger antisymmetric component observed in older adults suggests a compensatory use of neural feedback to offset this decline in strength and/or stiffness.…”
Section: Stiffnessmentioning
confidence: 58%
“…Shear waves are generated into the tissue by acoustic radiation force, and then the velocity of wave propagation is estimated and used for elasticity calculation [19,[21][22][23]. Most previous studies have emphasized measuring the stiffness of the musculotendinous structures of the lower extremities in the context of sports medicine [24][25][26][27] and certain diseases [28][29][30][31]. On the other hand, a few research studies applying the method to the upper limb muscles have been reported [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…To the Editor: We read with great interest regarding a recently published article titled "Shear Wave Elastography for Detecting Calf Muscle Stiffness an Effective Tool for Assessing Sarcopenia." 1 The authors included 65 healthy controls and 65 patients with sarcopenia, confirmed by the 2019 Asian Working Group for Sarcopenia (AWGS) diagnostic criteria. 2 Shear wave sonoelastography had been applied on stiffness assessment of the tibialis anterior, medial gastrocnemius, and soleus muscles.…”
mentioning
confidence: 99%